Self-Governance in the Cities of Getmanshchyna under the Magdeburg Law - Kobilec'kij, Mikola (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The article deals with the research of the issues of local self-governance in the cities of Getmanshchyna under the Magdeburg law. On the basis of the analysis of special scientific legal literature the author substantiates, that the Magdeburg law of Germanshchyna is the Ukrainian Municipal law. The judicature was provided under the provisions of Magdeburg law, Lithuanian Statute and customary law.
Keywords: prawo magdeburskie; samorząd; Hetmańszczyzna